The spiral code of prime numbers - Cameron, Vinoo (International Journal of Applied Mathematical Research, 2013)
Notice: The Final Frontier in Mathematics: The author has nearly finished work on the polarity of the divergence/convergence of the half line prime number values described for the first time in history by this author. Thus the spiral calculus will be unraveled in time and all prime number placements identified and predicted. The stated values at 30 constant for the half line values are as follows. The, following are the divergence codes for the half-line numbers at 1:3, (10*3). SIMPLE BASIC MATHEMATICS!!! . The “sui generis” for prime number variability at 1:3 divergences is based on the following line values at 10*3 Constant. 12=+6 14=+2 16=-2 18=-6 20=-10 22=-14 24=-18 28=-26 30=-30 32=-5 34=-7 36=-42 The, value at 100 half value is -170 The readers will not be offered the final work on the spiral calculus, which is the so called “mathematical writing on the wall”, a no brainer. The author will complete that on his own time, and current mathematicians are invited to finish it too without that inspiration of George Riemann/ Einstein, etc. The author first confirms the divergence/ convergence of 19 here at exact 1:3 and 1:6 as per well published manuscripts. Secondly the author presents a continuous prime number sieve at proportion 6, which is mathematically distinct from the sieve of Eratosthenes, first in history, tested by 10 million sieved numbers. Thirdly the author presents the half-line value of each and every prime number, and that is the first in history to present the spiral placement of prime number this is the evidence for a spiral placement of prime number and the essential half-line values. The unique relationship of space is presented here as a signature equation, based on the published divergence of empty space at 1:3 and 1:6 The gist of this manuscript is the clear mathematical proof that there is a mathematical disconnect between the linear mathematics as developed by man, and the primordial spiral planes and the half- line placement of the spiral /conal progression of mathematics. It is one thing to devise a linear prime number sieve and totally another to count prime numbers by their spirals and half – line placements. Thus mathematics could never come to term with the spiral planes of the universe of mathematics, except by indirectly placing the spiral sieve into a placement shown here by converting the linear sieve into a spiral sieve.